Origin-independent replication in Haloferax volcanii: RadA localisation, R-loops, and genomic rearrangements - Hodson, Katie (2023)
DNA replication typically initiates at origins, DNA sequences at which replication initiator proteins bind and instigate formation of the DNA replication machinery. It was thought that origins of replication are essential across all domains of life. However, the halophilic archaeon Haloferax volcanii can survive in the absence of origins, and in fact, strains lacking origins grow more quickly than the wild-type strain. When all origins are deleted, the archaeal RecA family recombinase RadA becomes essential. It is for this reason that it is thought that in the absence of origins, H. volcanii employs recombination-dependent replication.